Collaborative Governance Approach in Prevention of Sexual Violence Against Children in Islamic Boarding School - Mustiqowati Ummul Fithriyyah; Cahaya Makbul; Monalisa (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
The seriousness of the Government in preventing sexual violence against children can be seen from the formation of Law of the Republic of Indonesia Number 35 of 2014 concerning child protection. Prevention of sexual violence against children needs to get more attention through collaboration carried out by stakeholders. Many cases are not reported because the victims are helpless and ashamed. Currently, prevention of sexual violence is only focused on rehabilitation, and not focused on the initial stages of prevention. This requires collaboration between actors to be able to build commitment and trust in carrying out prevention. The purpose of this study is to describe collaborative governance in preventing sexual violence against children in Islamic boarding schools in Rian Province. This study uses a descriptive qualitative research method with data collection methods through stages of observation, interviews, and documentation. The research sample consisted of 30 people. The existing data is grouped, analyzed and summarized the findings. The results of this study are that collaboration between stakeholders is quite good, this can be seen from the full awareness of stakeholders to be able to synergize in preventing sexual violence in Islamic boarding schools. The Pekanbaru City Women's Empowerment, Child Protection and Community Empowerment Service provides educational information and socialization to the community so that children do not become perpetrators and victims of sexual violence. The formation of the PPKS task force is the beginning of the process of preventing sexual violence in Islamic boarding schools.